Relación entre la oscilación medio-lateral del pie, durante la estática, y las torceduras y esguinces de tobillo previos - Serrano Moreno, María Ángeles (Revista Internacional de Ciencias Podológicas, 2007)
This study tries to determine how is stability in the medio-lateral direction of the center of force of the ankle joint axis, during quiet standing and barefoot, before the production of ankle sprains. This result is going to compare with feet that haven´t ankle sprains to establish a connection of similarity or diference between two situations.